Traffic data analysis and visualization via Iterative Data Image Rotated Bar Graph (iDIRBrG) Method (Philippine computing journal)
In this paper, we present a visualization method known as the iteractive Data Image Rotated Bar Graph (iDIRBrG)Method that is capable of handling visualizations for large time seriestraffic data set...